Exogenous treatment and endogenous factors: Vanishing of omitted variable bias on the interaction term - Olena Y. Nizalova; Irina Murtazashvili (Institute for the Study of Labor (IZA), 2012)
Whether interested in the differential impact of a particular factor in various institutional settings or in the heterogeneous effect of policy or random experiment, the empirical researcher confronts a problem if the factor of interest is correlated with an omitted variable. This paper considers circumstances under which the estimate of the mentioned effect is consistent. We find that if the source of heterogeneity and omitted variable are jointly independent of policy or treatment, then the OLS estimate on the interaction term between the treatment and endogenous factor turns out to be consistent.
urn:nbn:de:101:1-201203064127
Keywords: C21; C93; 330; treatment effect; heterogeneity; policy evaluation; random experiments; omitted variable bias; Wirkungsanalyse; Methode der kleinsten Quadrate; Test